Prinsip Kesantunan dalam Tuturan Akun Tiktok “Riezky.Kabah” - Falah Jauhari; Anindha Naila Shofa; Zuyyinatul Mushoffa; Achmad Fahman Alkahfi; Nanda Fatimatuz Zahro; Paramita Kusuma Wardani; Asep Purwo Yudi Utomo (Jurnal Pendidikan dan Sastra Inggris, 2025)
The development of digital technology, especially social media platforms such as TikTok, has had an impact that has driven changes in communication culture in society, one of which is related to the phenomenon of politeness crisis. This study aims to analyze the application of the principle of politeness in language in the speech used by the owner of the TikTok account "riezky.kabah". The method used in this study is a qualitative descriptive methodological approach and a pragmatic theoretical approach with SBLC (Simak Bebas Libat Cakap) data collection techniques and notes. The data source in this study was taken from video uploads on the TikTok account "riezky.kabah" in the period 2023-2025. The data for this study is in the form of speech in the video, especially video content with a school background as a limitation in data analysis. The results of the interim analysis show that there are 2 utterances of compliance and 50 utterances of violation, with details of the maxim of wisdom (tact maxim) found compliance as much as 1 data and violation as much as 13 data, the maxim of generosity (generosity maxim) found violation as much as 13 data, the maxim of modesty (modestness maxim) found compliance as much as 1 data and violation as much as 3 data, the maxim of approval (approval maxim) found violation as much as 18 data, the maxim of agreement (agreement maxim) found violation as much as 2 data, and the maxim of sympathy (sympathy maxim) found violation as much as 1 data.